Prilog istraživanju likovne kritike u Hrvatskoj - peto desetljeće - Galjer, Jasna (1998)
That artistic creation and the context it stems froma are inseparable is considered to be an undoubtedly proven historic fact. There is also no doubt that tendenciously plays a part in it, but in spite of numerous theories the question of how big a part it can have in art remains open. in the multitude of various exaples, tzhat 20th century is so abundant with, actually more abundant than entire previous history of art, the expirience of the two totalitarian regimes are the most illustrative ones. Although bearing opposite ideological prefixes, National Socialismand Realsocialism have far more incommon in the mannier of likeness than differences. Both deny art has any indenpendence besides serving the regime propaganda, which needs a sutable frame for an image of idealised reality, as wellas an equaly deistorted ideal of beauty. Excepta writers, most Croatian artists, architects and Fine Arts critics who established themseves in the past, have been active during the entire fifth decade, when the culturale scne of these parts was marked by strong clashes about different attitudes in respect to the subject of the tendency in art, known as the leftists conflict, this period is characterised by an absence of polemics. Ideas as an expression of the national spirit have been a part of the Croatian Modern Artand its criticism from the begining in the century. Starting with Meštrovićs cycles originated in the Vienna Secessio, through attenpted rationalisationof the theory of the national expression, thay have paradoxically experienced their climax in fascist regime, when they pose as the main subject.
Projekt MZOS
HRV